Towards a Philosophy of Mediterranean Resistance: The Sahrawi Women’s Struggle - Paulizzi, Laura (I.S. MED. - Interdisciplinary Studies on the Mediterranean, 2025)
This communication aims to explore the cultural complexity of the Mediterranean region not so much from a geopolitical perspective, but rather as an open and metaphysically conceived cultural space. This perspective is analyzed through the political and social experience of Sahrawi women in Western Sahara, who have played a leading role in building and administering a democracy founded on steadfast and radical resistance. Firstly, it will emerge how the absence of patriarchal logics has created favorable conditions for this political experience, which took shape with the establishment of the Union nationale des femmes sahraouies (UNFS). Secondly, the core principles of this movement will be linked to key aspects of feminist theories that enrich the Mediterranean and global debate, particularly Islamic feminism (Fatima Mernissi et Asma Lamrabet), Ecofeminism (Vandana Shiva, Maria Mies), and Decolonial feminism (drawing from Françoise Vergès’ work). Such a comparison allows for a rethinking of concepts such as tradition, no longer as a synonym for immobility, and for a reconsideration of the Mediterranean space in light of cultural intersections and anti-colonial resistances, freeing it from a patriarchal, Eurocentric, and Islamophobic vision.